2011
DOI: 10.1038/ncb2204
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal positioning coordinates cellular nutrient responses

Abstract: Mammalian target of rapamycin (mTOR) signalling and macroautophagy (henceforth autophagy) regulate numerous pathological and physiological processes including cellular responses to altered nutrient levels. However, the mechanisms regulating mTOR and autophagy remain incompletely understood. Lysosomes are dynamic intracellular organelles 1, 2 intimately involved both in the activation of mTOR complex 1 (mTORC1) signalling and in degrading autophagic substrates 3-8. Here we report that lysosomal positioning coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

75
868
6
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 778 publications
(966 citation statements)
references
References 43 publications
75
868
6
1
Order By: Relevance
“…As previously described (Korolchuk et al., 2011), we found that upon removal of serum, the fraction of AVs in the perinuclear region increased about twofold in the fibroblasts from young mice. However, this juxtanuclear relocalization was severely blunted in old mice fibroblasts(Figure 2a,b).…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…As previously described (Korolchuk et al., 2011), we found that upon removal of serum, the fraction of AVs in the perinuclear region increased about twofold in the fibroblasts from young mice. However, this juxtanuclear relocalization was severely blunted in old mice fibroblasts(Figure 2a,b).…”
Section: Resultsmentioning
confidence: 75%
“…In agreement with our steady‐state observations, movement of autophagic vesicles toward the cellular periphery was significantly greater in primary fibroblasts from old mice than from young mice (Figure 3h). Serum removal did not significantly change the overall motility of APG in young cells (Figure 3i,j) but, as previously described (Korolchuk et al., 2011), it switched their microtubule directionality toward the perinuclear area (Figure 3k). Removal of serum in fibroblasts from old animals resulted in a significant increase in APG motility (Figure 3i,j) and partially reverted the directionality of these vesicles (Figure 3k).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Important for the spatial regulation of endosomal signaling, we are addressing in this review, is a finding described a few years ago that lysosomal positioning regulates the protein kinase complex mTORC1 activity [Korolchuk et al, 2011]. It was shown in this study that lysosomes move more closely to the plasma membrane in response to nutrient availability, whereas starvation causes perinuclear clustering of the organelles facilitating autophagy.…”
Section: Combinatorial Therapy and Future Prospectsmentioning
confidence: 65%
“…Finally, the presence of amino acids allows the activation of mTOR by Rheb, in part through the Rag GTPase-mediated translocation of mTOR to the lysosomal surface (Sancak et al, 2010). Amino-acid starvation, which inhibits mTOR, also facilitates autophagosome-lysosome fusion through lysosome clustering (Korolchuk et al, 2011).…”
Section: Physiological Control Of Autophagy: Mtormentioning
confidence: 99%